Comportamiento agronómico de tres híbridos de pepino (Cucumis sativus) con diferentes sistemas de tutorados en la época seca en la zona de Mocache. - Álava Montalván, Adrian Alberto (2017)
The present research was carried out in order to establish the hybrid of greater yield and profitability, for this we evaluated the agronomic behavior of three cucumber hybrids (Cucumis sativus) with two mentoring systems in the dry season in the area of Mocache .We used the Complete Blocks Random Design with 3x2 factorial arrangement in 3 replicates and all variables were analyzed by variance to establish the statistical difference and the DMS and Tukey 95% tests to determine the statistical difference of means between the factors and levels. The research was carried out at the Experimental Farm "La María" owned by the Quevedo State Technical University (UTEQ), located on the road Quevedo-El Empalme at km 7.5 of the Province of Los Ríos. The hybrids used were Modan RZ F1, Diamante and Darlington, with mesh and piola systems, implanted in a 20m x 20m field in which the performance of 666.66 plants was evaluated exactly under the effect of the two systems of I tutored thus reporting that the hybrid Mohamed with the mesh tutoring generated the highest yield but at the high cost of implementation, it is not profitable to use it in the dry season; unlike the hybrid Modan with the tutoring of piola that presents low performance in comparison with the aforementioned, but the higher is the one that has to pay for the low cost. All the hybrids together with the mesh tutoring have high yields ranging from 9443.20 kg / ha to 20036.53 kg / ha, but with a lower profitability ranging from -17,084% to 54,257%, being very different from the same hybrids but with the energy storage system being extracted from less than 8575.56 kg / ha to 9140.53 kg / ha, obtaining a higher profitability than from 21,561% to 59,475%, resulting in the Diamond hybrid under the 2 storage systems of information in low constancy in both yield and profitability. Keywords: behavior, hybrids, tutoring.